The Justice Dimensions in the Provision of Al-'Awl on Islamic Inheritance Law - Taqiyuddin, Hafidz (Hikmatuna : Journal for Integrative Islamic Studies, 2021)
This study focuses on the justice contained in al-'awl as a part of the inheritance system in Islam. For some people, justice in the Islamic inheritance is a form of injustice, and others consider it proportional justice. Therefore, tracing how the value of justice in the initial concept is a challenge in itself. Moreover, the concept of Al-Awl is considered as a reduction of existing parts. In addition, this article also focuses on the problem of the distribution of Al-Awl's manifestations with the provisions of God's law. This research used a qualitative method with a philosophical-theological approach to answering this question. This study shows that al-Awl in the Islamic inheritance system is closely related to the value of justice. This is because al-Awl shows equality by reducing legal provisions to avoid conflicts between family members, not injustice or proportional justice. Al-Awl is a solution to reduce the definite portion of all heirs proportionally, which is a way out that provides the general benefit compared to reducing the definite portion of some heirs. In addition, al-Awl's concept is a manifestation of the acceptance of God's law in the destiny of death and the reality of the remaining family structure.